A bishopric under the scrutiny of the viceroy and a prelate jealous of his jurisdiction: The insights of the count of Galve and Manuel Fernandez de Santa Cruz before the Council of Indies: 1696 and 1697 - Flores Sosa, Emmanuel Michel (2021)
This paper is about the correspondence of the Royal Agreement of Mexico and the bishop Santa Cruz with reference to some developments in the city of Puebla in 1696. These letters were sent to the Council of Indians and represent the last chapter of the confrontation between these authorities.